2023
DOI: 10.3390/vetsci10010046
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Feline Upper Respiratory Tract Infection Encourages a Geographically Specific FCV Vaccine

Abstract: A total of 1158 cats with feline upper respiratory tract infection were incorporated from twenty animal hospitals in Wuhan, China, from April 2019 to April 2022 to investigate the epidemiology of feline calicivirus (FCV), herpesvirus-1 (FHV-1), Mycoplasma felis (M. felis) and Chlamydia felis (C. felis) for the development of a geographically-specific FCV vaccine with reference to prevalence and risk factors for infection. The 871 samples (75.2%) of kittens were younger than 12 months, of which 693 were males, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
3
4
0
1
Order By: Relevance
“…In this study, FHV-1 showed a higher positivity rate in winter compared to summer, while FCV exhibited a higher positivity rate in summer than in winter, consistent with the findings reported by Gao et al [ 20 ]. This variation may be related to the physical and chemical properties of the viruses themselves.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, FHV-1 showed a higher positivity rate in winter compared to summer, while FCV exhibited a higher positivity rate in summer than in winter, consistent with the findings reported by Gao et al [ 20 ]. This variation may be related to the physical and chemical properties of the viruses themselves.…”
Section: Discussionsupporting
confidence: 92%
“…The continuous evolution of FCV viruses poses challenges to vaccine design [ 34 ]. Several studies have indicated that vaccine strains used over decades may have become less effective, and that there are differences in neutralizing titers between FCV epidemic isolates from different regions and vaccine strains, which has also been confirmed by our previous research [ 27 , 29 ]. The FCV-255 inactivated vaccine widely used in China has limited in vitro cross-neutralizing potency against the Chinese epidemic strains, and it may not provide effective protection [ 22 , 30 , 35 ].…”
Section: Discussionsupporting
confidence: 84%
“…Cats with a history of immunization are still susceptible to new epidemic strains [ 26 ]. The persistent high mutability of FCV epidemic strains has greatly increased the clinical demand for new FCV vaccines [ 27 ]. Therefore, the diversity of FCV genotypes should be taken into account in the development of new FCV vaccines [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…FCV is a nonenveloped, positive-sense, ssRNA virus that belongs to the family Caliciviridae [6,14], and its 7-8 kb RNA genome has three ORFs, ORF1, ORF2 and ORF3 [3,6,15]. Notably, ORF2 encodes the capsid protein VP1, which includes six regions, and regions C and E are variable; thus, new mutated strains are constantly emerging [3,6,9,16]. Although commercial vaccines have been approved for preventing FCV-induced disease, whether the existing commercial vaccines exhibit cross-protection against the newly emerging FCV strains is unknown [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although commercial vaccines have been approved for preventing FCV-induced disease, whether the existing commercial vaccines exhibit cross-protection against the newly emerging FCV strains is unknown [3,9]. Since the prevention and control of the disease are limited, it is necessary to find and develop novel antiviral compounds [16]. Previous studies have discovered that several compounds, including sinefungin, poly (sodium 4-styrenesulfonate), the analogue NITD008, nitazoxanide, mefloquine, copper chloride and mizoribine, have antiviral activities [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%